The Effect of Supervision and Task Planning on the Performance of the Depok Metro Resort Police Personnel, Polda Metro Jaya - Saipul Rohman; Harries Madiistriyatno; Widya Nengsih (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of supervision and task planning on the performance of Depok Metro Police personnel, Polda Metro Jaya, both partially and simultaneously. Personnel performance is a key factor in supporting the effectiveness of police duties, so an optimal supervision system and structured and directed task planning are needed. The research approach used is quantitative research, namely research that emphasizes the processing of numerical data obtained from respondents, supported by qualitative data in the form of statements in questionnaires and the results of limited consultations and interviews as analytical reinforcement. The population in this study amounted to 133 Depok Metro Police personnel, with a sample of 100 respondents determined using a proportional sampling technique. Data collection was carried out by distributing questionnaires with a Likert scale arranged based on the indicators of each research variable. Data analysis and hypothesis testing techniques were carried out using Structural Equation Modeling–Partial Least Square (SEM-PLS) version 4.0, which was chosen because it is able to analyze relationships between variables simultaneously and complexly. The results of the study indicate that supervision (X1) has a positive and significant effect on personnel performance (Y), as well as task planning (X2) has a positive and significant effect on personnel performance (Y) partially. In addition, simultaneous supervision and task planning were proven to have a significant effect on the performance of Depok Metro Police personnel. The coefficient of determination (R-Square) value of 0.441 indicates that 44.1% of the variation in personnel performance can be explained by the supervision and task planning variables, while the remaining 55.9% is influenced by other factors outside the research model